Financial protection in the UK building industry - Hughes, Will 1956- (Thomas Telford, 1998)
Drawing from the Reading Construction Forum, this report clarifies the various options open to the various parties and stakeholders in the construction process. It considers the problem of financial protection, and clearly lays out the alternative solutions.